Avian Podocytes, Which Lack Nephrin, Use Adherens Junction Proteins at Intercellular Junctions. (January 2016) - Yaoita, Eishin; Nishimura, Hiroko; Nameta, Masaaki; Yoshida, Yutaka; Takimoto, Hiroki; Fujinaka, Hidehiko; Kawachi, Hiroshi; Magdeldin, Sameh; Zhang, Ying; Xu, Bo; Oyama, Tomizo; Nakamura, Fujio; et al.
Nephrin, a major intercellular junction (ICJ) molecule of mammalian podocytes in the renal glomerulus, is absent in the avian genome. We hypothesized that birds use ICJ molecules other than nephrin in their podocytes. Therefore, in the present study, we examined the possible involvement of adherens junction (AJ) proteins in the ICJs of avian podocytes. We found the AJ proteins N-cadherin and α- and β-catenins in podocytes of quail and chickens but not in those of rats, pigs or humans. The AJ proteins were prominent in avian glomerulus-rich fractions in immunoblot analyses, and in immunofluorescence microscopy analyses, they were localized along glomerular capillary walls appearing in at least two staining patterns: weakly diffuse and distinctly granular. Immunoelectron microscopy demonstrated that the significant accumulation of immunogold particles for the AJ proteins were especially evident in avian slit diaphragms and AJs. Furthermore, N-cadherin was found to be expressed in all nephron cells in the early developmental stage but became confined to podocytes during maturation. These results indicate that avian slit diaphragms clearly express AJ proteins as compared with that in the mammal—where AJ proteins are suppressed to an extremely low level—and that avian podocytes are interconnected by AJs per se in addition to slit diaphragms.